Acquisition of Vocabulary of ESL Engineering Students through a Newspaper: An Empirical Study (Pascasarjana Universitas Negeri Makassar, 2022)
Vocabulary plays a vital role for an effective communication and fluent language usage among ESL (English as Second Language) learners. Newspaper reading helps the students to develop vocabulary level beyond the classroom. The present empirical study assesses the participants’ vocabulary level by using a newspaper article. Based on the aim of this empirical study, it was decided that the best method for this investigation to better understand the levels of the students is to adopt the qualitative and quantitative research design. To find out the vocabulary level of the participants this research developed a questionnaire. A total of ten open ended questions are framed in this questionnaire. Based on the collected data the findings explored that, the participants’ have vocabulary gaps. The findings of this study also revealed that, the student participants’ vocabulary level is not up to the excepted mark. The randomly selected undergraduate engineering students (n=142) have taken the part in this study. Finally, this empirical study was concluded with recommendations to the participants to improve vocabulary knowledge.